1984
DOI: 10.1149/1.2115556
|View full text |Cite
|
Sign up to set email alerts
|

Halide Nuclei Theory of Pit Initiation in Passive Metals

Abstract: A kinetic approach is used to test the theory of pit initiation in passive metals in contact with a solution containing aggressive ions. A new process, hemispherical halide nuclei formation at the surfac.e of the passive film and inward growth under restricted conditions, is introduced. The possibility of nuclei growth is discussed, taking into account the irreversible thermodynamic stability of the system. The direction of the irreversible change of a system consisting of the metal substrate, the passive film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 19 publications
1
35
0
Order By: Relevance
“…Only three of these theories are analytic, in the sense that they yield analytical relationships between measurable parameters and various independent variables that can be tested experimentally [1]. In particular, the Point Defect Model (PDM) of Lin, Chao, and of Macdonald [28] (later modi®ed by Ellerbrock & Macdonald [28]) and the halide nucleus model of Okada [36] provide analytical expressions for both critical breakdown parameters (V c , t ind ). Experimental evaluations of various theories and models by Lei et al [37] and, in particular, by Milosev and co-workers [38] have shown that only the PDM is consistent with the experimental data for the systems investigated.…”
Section: Theories and Modelsmentioning
confidence: 99%
“…Only three of these theories are analytic, in the sense that they yield analytical relationships between measurable parameters and various independent variables that can be tested experimentally [1]. In particular, the Point Defect Model (PDM) of Lin, Chao, and of Macdonald [28] (later modi®ed by Ellerbrock & Macdonald [28]) and the halide nucleus model of Okada [36] provide analytical expressions for both critical breakdown parameters (V c , t ind ). Experimental evaluations of various theories and models by Lei et al [37] and, in particular, by Milosev and co-workers [38] have shown that only the PDM is consistent with the experimental data for the systems investigated.…”
Section: Theories and Modelsmentioning
confidence: 99%
“…It may be due to the fact that rotation stabilized the system and thus copper achieved a stable passive state at a smaller inhibitor concentration. As shown previously [3], copper PC in background solution (0.1 M NaHCO 3 + 0.01 M NaCl) occurs by an adsorption-penetration mechanism (with participation of an insoluble CuCl particle as an activator), corresponding to T. Okada's theory [4]. The protective action of BTAH is due to its high adsorption ability and formation of a dense insoluble copper benzotriazolate film on the metal surface [5].…”
Section: Addition Of 1·10mentioning
confidence: 72%
“…The physical models for the repassivation potential also include the nucleation process. For example, Okada [43] formulated the repassivation potential, based on the oxide reformation in the occluded area, as the criterion for the repassivation. Therefore, the induction times for repassivation (i.e.…”
Section: Induction Timementioning
confidence: 99%